SDGs, health and the G20: A vision for public policy - Sunisha Neupane; Zoe Boutilier; Ilona Kickbusch; Ali Mehdi; Miriam Sangiorgio; Michaela Told; Peter Taylor (Kiel Institute for the World Economy (IfW), 2018)
Ensuring "health for all" remains a persistent and entrenched global challenge. G20 governments are in a position to elevate the priority accorded to health, and acknowledge the centrality of health to attaining the SDGs. The authors call on G20 leaders to build nations that are more inclusive and less divided, by: adopting a Health- in-All-Policies approach, prioritizing the most vulnerable, engaging citizens in policy processes, and filling health data gaps.
Keywords: I1; I18; 330; sustainable development goals; SDGs; goal 3; global health; engagement; health policy